A high entropy oxide ceramic coating on magnesium alloy surface and preparation method thereof

By using micro-arc oxidation technology to generate high-entropy oxide ceramic coatings in situ on the surface of magnesium alloys, the problem of preparing coatings on the surface of low-melting-point magnesium alloys has been solved, and the preparation of high-entropy oxide ceramic coatings at low temperatures has been achieved, thereby improving the corrosion resistance and hardness of magnesium alloys.

CN120556111BActive Publication Date: 2025-10-28NORTHEASTERN UNIV CHINA
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202511081892.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-08-04
Publication Date
2025-10-28
Estimated Expiration
2045-08-04

AI Technical Summary

Technical Problem

Existing technologies make it difficult to prepare high-entropy oxide ceramic coatings on the surface of low-melting-point magnesium alloys, and traditional high-temperature sintering or thermal spraying technologies are costly and complex, making them unsuitable for magnesium alloys.

Method used

A high-entropy oxide ceramic coating was generated in situ on the surface of a magnesium alloy using micro-arc oxidation technology. The coating consisted of Mg, Zr, Ti, Al, V, O, and F. It was prepared at low temperature using a micro-arc oxidation device, and the coating thickness was 15μm-20μm.

Benefits of technology

A method for preparing high-entropy oxide ceramic coatings at low temperatures has been achieved, resulting in strong adhesion, uniform element distribution, excellent corrosion resistance and hardness, thus expanding the application range of magnesium alloys.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120556111B_ABST
    Figure CN120556111B_ABST
Patent Text Reader

Abstract

This invention discloses a high-entropy oxide ceramic coating for magnesium alloy surfaces and its preparation method, belonging to the field of magnesium alloy surface treatment technology. The elemental composition of this high-entropy oxide ceramic coating includes metallic elements, O, and F, specifically Mg, Zr, Ti, Al, and V. The high-entropy oxide ceramic coating is grown in situ on the magnesium alloy substrate surface, consisting of MgO, ZrO2, TiO2, Al2O3, V2O3, and MgF2, with a thickness of 15μm-20μm. This invention prepares a high-entropy oxide ceramic coating on magnesium alloy surfaces using micro-arc oxidation technology, offering advantages such as low processing temperature, minimal thermal impact on the substrate, strong in-situ bonding, high elemental uniformity, no interface contamination or oxidation loss, greater adaptability to complex shapes, low environmental pollution, and short processing cycle and low cost. It enables the preparation of high-entropy oxide ceramic coatings on low-melting-point metal surfaces such as magnesium alloys, expanding the application range of magnesium alloys.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of magnesium alloy surface treatment technology, specifically relating to a high-entropy oxide ceramic coating on magnesium alloy surface and its preparation method. Background Technology

[0002] Magnesium alloys are the lightest metals among structural materials, possessing high specific strength, specific stiffness, specific elastic modulus, as well as good damping properties, impact resistance, weldability, and dimensional stability. They are also hailed as the "metal of the 21st century" due to their excellent thermal conductivity, recyclability, electromagnetic interference resistance, and excellent shielding performance. These properties have led to the widespread application of magnesium alloys in the automotive, energy, electronics and communications, computer, aerospace, and defense industries. However, the high reactivity, poor thermal stability, and poor wear and corrosion resistance of magnesium alloys have become key factors restricting their ability to achieve many of their other properties.

[0003] High-entropy oxide ceramics are a new type of ceramic material, typically composed of five or more metallic elements combined with oxygen. Compared to traditional ceramic materials, high-entropy oxide ceramics have a higher entropy value, meaning stronger randomness in atomic positions, resulting in superior high-temperature resistance, chemical stability, and wear and corrosion resistance. Therefore, preparing high-entropy oxide ceramic coatings on magnesium alloy surfaces can significantly improve their various properties and expand the application range of magnesium alloys. However, current preparation methods for high-entropy oxide ceramic coatings primarily employ high-temperature sintering or thermal spraying, which are complex processes requiring high-temperature treatment and are not suitable for magnesium alloys with low melting points. Chinese patent CN 14606457A discloses a high-entropy alloy oxide coating and its preparation method, which involves mechanically ball-milling pure metal powder, plasma-spraying a CuMnCoFeNi high-entropy alloy coating, and high-temperature, high-oxygen, high-pressure thermal growth to form a composite conductive oxide coating. This method is energy-intensive and costly, and because it requires high-temperature, high-pressure thermal oxidation to generate the high-entropy alloy oxide coating, it is not suitable for light metal alloys with low melting points. Chinese patent CN115971011A discloses a high-entropy composite oxide hydrogen-barrier coating and its preparation method. The method involves preparing a metal salt dry gel by sol-gel method, pre-sintering the dry gel, grinding it to obtain a precursor powder, fully dissolving the precursor powder in a solvent, and spraying it onto the surface of a metal sample under high pressure. Finally, the high-entropy oxide coating is prepared by high-temperature sintering. The implementation steps are complex, and high-temperature sintering is not suitable for magnesium alloys with low melting points. Summary of the Invention

[0004] To address the problems existing in the prior art, the present invention aims to provide a high-entropy oxide ceramic coating on the surface of magnesium alloys and its preparation method. This method is suitable for magnesium alloys with low melting points. It achieves in-situ generation of high-entropy oxide ceramic coating on the surface of magnesium alloys at a lower process temperature through micro-arc oxidation technology. This method has advantages such as minimal thermal impact on the magnesium alloy substrate, strong adhesion to the magnesium alloy substrate, high uniformity of element distribution, and no interface contamination or oxidation burn-off.

[0005] The objective of this invention is achieved through the following technical solution:

[0006] This invention provides a high-entropy oxide ceramic coating on the surface of a magnesium alloy. The elemental composition of the high-entropy oxide ceramic coating includes metallic elements, O and F, wherein the metallic elements are Mg, Zr, Ti, Al and V. The high-entropy oxide ceramic coating is grown in situ on the surface of a magnesium alloy substrate and is composed of MgO, ZrO2, TiO2, Al2O3, V2O3 and MgF2, with a thickness of 15μm-20μm.

[0007] Furthermore, the atomic percentages of the elements in the high-entropy oxide ceramic coating are: Mg: 14.5%-23.0%, Zr: 6.0%-7.5%, Ti: 5.5%-7.0%, Al: 5.0%-6.0%, V: 5.5%-6.5%, O: 48.0%-52.5%, and F: 5.5%-7.0%.

[0008] Furthermore, magnesium alloy matrices include LA103Z, AZ31B, and ZK61M, among others.

[0009] This invention also provides a method for preparing a high-entropy oxide ceramic coating on a magnesium alloy surface, the specific steps of which include:

[0010] (1) Pretreatment of magnesium alloy matrix;

[0011] (2) Prepare a multi-component composite electrolyte containing the metal elements required for the high-entropy oxide ceramic coating;

[0012] (3) The magnesium alloy substrate from step (1) is clamped in a hanger and placed in the oxidation tank of the micro-arc oxidation equipment. The multi-component composite electrolyte from step (2) is added to the oxidation tank. The magnesium alloy substrate is completely immersed in the multi-component composite electrolyte for micro-arc oxidation treatment.

[0013] Further, in step (1) the pretreatment is to use a sandblasting machine to sandblast the magnesium alloy substrate, then use compressed air to blow the magnesium alloy surface clean, and then use low, medium and high mesh water-resistant sandpaper to polish the magnesium alloy step by step, and finally perform ultrasonic cleaning and drying for later use.

[0014] Furthermore, the sand used for sandblasting is made of zirconium oxide with a particle size of 150 mesh and a pressure of 0.3 MPa;

[0015] Water-resistant sandpaper with low, medium, and high mesh counts is available in 320#, 600#, and 1000#.

[0016] Ultrasonic cleaning involves ultrasonic cleaning in anhydrous ethanol for 10 minutes.

[0017] Furthermore, the electrolyte of the multi-component composite system in step (2) is composed of sodium citrate, ammonium fluorozirconate, ammonium fluorotitanate, ammonium fluoroaluminate, ammonium metavanadate, sodium pyrophosphate, and triethanolamine.

[0018] Furthermore, the specific preparation process of the multi-component composite electrolyte is as follows: 20 g / L-40 g / L sodium citrate, 10 g / L-20 g / L ammonium fluorozirconate, 10 g / L-20 g / L ammonium fluorotitanate, 10 g / L-20 g / L ammonium fluoroaluminate, 10 g / L-20 g / L ammonium metavanadate, 5 g / L-10 g / L sodium pyrophosphate, and 10 mL / L triethanolamine are sequentially added to deionized water, while continuously stirring until completely dissolved, thus preparing the multi-component composite electrolyte.

[0019] Furthermore, in step (3), the magnesium alloy substrate is used as the anode, the stainless steel sheet is used as the cathode, the power supply is set to constant voltage working mode, the electrolyte temperature is controlled, and the process parameters of micro-arc oxidation treatment are adjusted.

[0020] Furthermore, the process parameters for micro-arc oxidation are as follows: voltage 450V-500V, frequency 1000Hz-1500Hz, duty cycle 10%, oxidation time 20min-25min, and the electrolyte temperature is controlled at 15℃-20℃ during the micro-arc oxidation process using a chiller.

[0021] Compared with the prior art, the present invention has the following advantages and effects:

[0022] 1. Compared with the high-temperature sintering method or thermal spraying technology currently used to prepare high-entropy oxide ceramic coatings, this invention prepares high-entropy oxide ceramic coatings on the surface of magnesium alloys through micro-arc oxidation technology. It has advantages such as low process temperature, small thermal impact on the substrate, strong in-situ bonding force, high uniformity of element distribution, no interface pollution and oxidation loss, stronger adaptability to complex shapes, less environmental pollution, and short process cycle and low cost. It can realize the preparation of high-entropy oxide ceramic coatings on the surface of low-melting-point metals such as magnesium alloys, thereby giving them better high-temperature resistance, chemical stability and wear and corrosion resistance, thus expanding the application range of magnesium alloys.

[0023] 2. This invention prepares a high-entropy oxide ceramic coating on the surface of magnesium alloy. Benefiting from the unique advantages brought by the high-entropy effect, the "cocktail effect" of multi-principal oxides can enhance the thermodynamic stability of the coating and inhibit crack initiation through lattice distortion and slow diffusion effect.

[0024] 3. Existing conventional magnesium alloy micro-arc oxidation coatings typically contain only 1-3 alloying elements. This invention prepares a high-entropy oxide ceramic coating on the surface of magnesium alloys. Due to the synergistic effect of multiple alloying elements such as Mg, Zr, Ti, Al, and V in the high-entropy oxide, a dense and chemically inert composite oxide layer (composed of MgO, ZrO2, TiO2, Al2O3, and V2O5) can be formed, significantly improving the corrosion resistance of magnesium alloys. Furthermore, the multi-component solid solution strengthening effect of the high-entropy structure can also significantly improve the coating hardness. Compared with magnesium alloy micro-arc oxidation coatings containing only 1-3 alloying elements, the high-entropy oxide ceramic coating prepared on the surface of magnesium alloys by this invention has better corrosion resistance and hardness. Attached Figure Description

[0025] Figure 1 This is a scanning electron microscope (SEM) image of the high-entropy oxide ceramic coating on the magnesium alloy surface in Example 1.

[0026] Figure 2 This is a scanning electron microscope (SEM) image of a cross-section of the high-entropy oxide ceramic coating on the magnesium alloy surface in Example 1.

[0027] Figure 3 The image shows the surface energy dispersive X-ray spectroscopy (EDS) analysis of the high-entropy oxide ceramic coating on the magnesium alloy surface in Example 1.

[0028] Figure 4 The image shows the X-ray diffraction (XRD) analysis of the high-entropy oxide ceramic coating on the magnesium alloy surface in Example 1.

[0029] Figure 5 This is an electrochemical polarization curve of the high-entropy oxide ceramic coating on the magnesium alloy surface in Example 1;

[0030] Figure 6 This is a scanning electron microscope (SEM) image of the high-entropy oxide ceramic coating on the magnesium alloy surface in Example 2.

[0031] Figure 7 This is a scanning electron microscope (SEM) image of a cross-section of the high-entropy oxide ceramic coating on the magnesium alloy surface in Example 2.

[0032] Figure 8 The image shows the surface energy dispersive X-ray spectroscopy (EDS) analysis of the high-entropy oxide ceramic coating on the magnesium alloy surface in Example 2.

[0033] Figure 9The image shows the X-ray diffraction (XRD) analysis of the high-entropy oxide ceramic coating on the magnesium alloy surface in Example 2.

[0034] Figure 10 This is an electrochemical polarization curve of the high-entropy oxide ceramic coating on the magnesium alloy surface in Example 2. Detailed Implementation

[0035] The present invention will now be described in detail with reference to the embodiments.

[0036] Example 1:

[0037] The present invention discloses a high-entropy oxide ceramic coating on a magnesium alloy surface. The high-entropy oxide ceramic coating contains Mg, Zr, Ti, Al and V as metallic elements, with atomic percentages of 14.56%:7.22%:6.78%:5.92%:6.40%, and also includes elements O and F, with atomic percentages of 52.28% and 6.84%, respectively. The magnesium alloy substrate is LA103Z, and the coating is grown in situ on the surface of the magnesium alloy substrate with a thickness of 20 μm.

[0038] The present invention discloses a method for preparing a high-entropy oxide ceramic coating on a magnesium alloy surface, which specifically includes the following steps:

[0039] (1) Pretreatment of magnesium alloy substrate: Select LA103Z magnesium alloy sheet with dimensions (length × width × thickness) of 15mm × 15mm × 3mm, and use a sandblasting machine to sandblast the LA103Z magnesium alloy with a sand particle size of 150 mesh and a pressure of 0.3Mpa. Then use compressed air to blow clean the surface of LA103Z magnesium alloy. Then use 320#, 600# and 1000# water-resistant abrasive paper to polish the LA103Z magnesium alloy step by step. Finally, ultrasonically clean it in anhydrous ethanol for 10 minutes and dry it for later use to complete the pretreatment.

[0040] (2) Prepare a multi-component composite electrolyte containing the metal elements required for the high-entropy oxide ceramic coating. Add 40 g / L sodium citrate, 20 g / L ammonium fluorozirconate, 20 g / L ammonium fluorotitanate, 20 g / L ammonium fluoroaluminate, 20 g / L ammonium metavanadate, 10 g / L sodium pyrophosphate, and 10 mL / L triethanolamine to deionized water in sequence, while stirring continuously until completely dissolved to prepare the multi-component composite electrolyte.

[0041] (3) The magnesium alloy substrate from step (1) is placed in the oxidation tank of the micro-arc oxidation equipment using a clamping device. The multi-component composite electrolyte from step (2) is added to the oxidation tank. The magnesium alloy substrate is completely immersed in the multi-component composite electrolyte as the anode, and a stainless steel sheet is used as the cathode. The power supply is set to constant voltage working mode. The micro-arc oxidation process parameters are adjusted for micro-arc oxidation treatment. The process parameters are: voltage 500V, frequency 1500Hz, duty cycle 10%, and oxidation treatment time 25min. During the micro-arc oxidation treatment, a chiller is used to control the electrolyte temperature at 15℃-20℃.

[0042] Performance Analysis:

[0043] (1) Characterization of coating morphology:

[0044] like Figure 1 As shown in the SEM image, compared with the porous and cracked characteristics of traditional micro-arc oxidation coatings, the high-entropy oxide ceramic coating grown in situ on the surface of LA103Z magnesium alloy in this embodiment 1 exhibits a lamellar and "cauliflower" morphological characteristics. The coating surface has fewer micropores and smaller pore sizes, and no obvious cracks, which is beneficial to improving the corrosion resistance of the coating.

[0045] like Figure 2 As shown in the SEM image, the high-entropy oxide ceramic coating of Example 1 is tightly bonded to the LA103Z magnesium alloy substrate. The coating is continuous and dense, with a thickness of up to 20 μm, which is beneficial to enhancing the corrosion resistance of the coating.

[0046] (2) Elemental composition analysis of the coating:

[0047] like Figure 3 As shown in the EDS diagram, the high-entropy oxide ceramic coating of Example 1 is composed of Mg, Zr, Ti, Al, V, O and F elements, and the specific element contents are shown in Table 1 below:

[0048] Table 1. Surface element content of the high-entropy oxide ceramic coating in Example 1:

[0049] ;

[0050] (3) Coating composition and hardness analysis:

[0051] like Figure 4 As shown in the XRD pattern, the main components of the high-entropy oxide ceramic coating in Example 1 are MgO, ZrO2, TiO2, V2O3, Al2O3 and MgF2. The high-entropy oxide coating has high hardness. Referring to the hardness test method of GB / T 4340-2009, the load is 25gf, and the hardness of the coating is measured to be 768HV.

[0052] (4) Corrosion resistance analysis:

[0053] The magnesium-lithium alloy with a high-entropy oxide ceramic coating on its surface in Example 1 was subjected to electrochemical polarization testing in a 3.5% NaCl solution. Figure 5 Calculations based on the electrochemical polarization curves show that the corrosion current Icorr of the LA103Z magnesium alloy with a high-entropy oxide ceramic coating is 8.724 × 10⁻⁶. -9 A / cm 2 The corrosion current of the LA103Z magnesium alloy matrix is ​​1.738 × 10⁻⁶. -4 A / cm 2 The high-entropy oxide ceramic coating exhibits a low corrosion current, which is reduced by five orders of magnitude, indicating that the coating has excellent corrosion resistance and provides good corrosion protection.

[0054] Example 2:

[0055] The present invention discloses a high-entropy oxide ceramic coating on a magnesium alloy surface. The metal elements in the high-entropy oxide ceramic coating are Mg, Zr, Ti, Al and V, with atomic percentages of 22.96%:6.46%:5.85%:5.07%:5.63%, and also include elements O and F, with atomic percentages of 48.35% and 5.68%, respectively. The magnesium alloy substrate is ZK61M, and the coating is grown in situ on the surface of the magnesium alloy substrate with a thickness of 15 μm.

[0056] The present invention discloses a method for preparing a high-entropy oxide ceramic coating on a magnesium alloy surface, which specifically includes the following steps:

[0057] (1) Pretreatment of magnesium alloy substrate: Select ZK61M magnesium alloy sheet with dimensions (length × width × thickness) of 15mm × 15mm × 3mm, and use a sandblasting machine to sandblast the ZK61M magnesium alloy with a sand particle size of 150 mesh and a pressure of 0.3Mpa. Then use compressed air to blow clean the surface of ZK61M magnesium alloy, and then use 320#, 600# and 1000# water-resistant abrasive paper to polish the ZK61M magnesium alloy step by step. Finally, ultrasonically clean it in anhydrous ethanol for 10 minutes and then dry it for later use to complete the pretreatment.

[0058] (2) Prepare a multi-component composite electrolyte containing the metal elements required for the high-entropy oxide ceramic coating. Add 20 g / L sodium citrate, 10 g / L ammonium fluorozirconate, 10 g / L ammonium fluorotitanate, 10 g / L ammonium fluoroaluminate, 10 g / L ammonium metavanadate, 5 g / L sodium pyrophosphate, and 10 mL / L triethanolamine to deionized water in sequence, while stirring continuously until completely dissolved to prepare the multi-component composite electrolyte.

[0059] (3) The magnesium alloy substrate from step (1) is placed in the oxidation tank of the micro-arc oxidation equipment using a clamping fixture. The multi-component composite electrolyte from step (2) is added to the oxidation tank. The magnesium alloy substrate is completely immersed in the multi-component composite electrolyte as the anode, and a stainless steel sheet is used as the cathode. The power supply is set to constant voltage working mode. The micro-arc oxidation process parameters are adjusted for micro-arc oxidation treatment. The process parameters are: voltage 450V, frequency 1000Hz, duty cycle 10%, and oxidation treatment time 20min. During the micro-arc oxidation treatment, a chiller is used to control the electrolyte temperature at 15℃-20℃.

[0060] Performance Analysis:

[0061] (1) Characterization of coating morphology:

[0062] like Figure 6 As shown in the SEM image, the high-entropy oxide ceramic coating grown in situ on the ZK61M magnesium alloy surface in Example 2 has few micropores and small pore size, and no obvious cracks, which is beneficial to improving the corrosion resistance of the coating.

[0063] like Figure 7 As shown in the SEM image, the high-entropy oxide ceramic coating of Example 2 is tightly bonded to the ZK61M magnesium alloy substrate. The coating is continuous and dense, with a thickness of up to 15 μm, which is beneficial to enhancing the corrosion resistance of the coating.

[0064] (2) Elemental composition analysis of the coating:

[0065] like Figure 8 As shown in the EDS diagram, the high-entropy oxide ceramic coating of Example 2 is composed of Mg, Zr, Ti, Al, V, O, and F elements, and the specific element contents are shown in Table 2 below:

[0066] Table 2 Surface element content of the high-entropy oxide ceramic coating in Example 2:

[0067] ;

[0068] (3) Coating composition and hardness analysis:

[0069] like Figure 9 As shown in the XRD pattern, the main components of the high-entropy oxide ceramic coating in Example 2 are MgO, ZrO2, TiO2, V2O3, Al2O3 and MgF2. Referring to the hardness test method of GB / T 4340-2009, the load is 25gf, and the hardness of the coating is measured to be 712HV.

[0070] (4) Corrosion resistance analysis:

[0071] The magnesium-lithium alloy with a high-entropy oxide ceramic coating on its surface in Example 2 was subjected to electrochemical polarization testing in a 3.5% NaCl solution. Figure 10 Calculations based on the electrochemical polarization curves show that the corrosion current Icorr of the ZK61M magnesium alloy with a high-entropy oxide ceramic coating is 4.352 × 10⁻⁶. -8 A / cm 2 The high-entropy oxide ceramic coating exhibits a low corrosion current, indicating that the coating has excellent corrosion resistance and provides good corrosion protection.

[0072] Example 3:

[0073] The present invention discloses a high-entropy oxide ceramic coating on a magnesium alloy surface. The high-entropy oxide ceramic coating contains Mg, Zr, Ti, Al and V as metallic elements, with atomic percentages of 18.17%:6.87%:6.03%:5.42%:5.97%, and also includes elements O and F, with atomic percentages of 51.33% and 6.21%, respectively. The magnesium alloy substrate is AZ31B, and the coating is grown in situ on the surface of the magnesium alloy substrate with a thickness of 17 μm.

[0074] The present invention discloses a method for preparing a high-entropy oxide ceramic coating on a magnesium alloy surface, which specifically includes the following steps:

[0075] (1) Magnesium alloy substrate pretreatment: Select AZ31B magnesium alloy sheet with dimensions (length × width × thickness) of 15mm × 15mm × 3mm. Use a sandblasting machine to sandblast the AZ31B magnesium alloy with a sand particle size of 150 mesh and a pressure of 0.3Mpa. Then use compressed air to blow clean the surface of the AZ31B magnesium alloy. Then use 320#, 600# and 1000# water-resistant abrasive paper to polish the AZ31B magnesium alloy step by step. Finally, ultrasonically clean it in anhydrous ethanol for 10 minutes and dry it for later use to complete the pretreatment.

[0076] (2) Prepare a multi-component composite electrolyte containing the metal elements required for the high-entropy oxide ceramic coating. Add 30 g / L sodium citrate, 15 g / L ammonium fluorozirconate, 15 g / L ammonium fluorotitanate, 15 g / L ammonium fluoroaluminate, 15 g / L ammonium metavanadate, 7.5 g / L sodium pyrophosphate, and 10 mL / L triethanolamine to deionized water in sequence, while stirring continuously until completely dissolved to prepare the multi-component composite electrolyte.

[0077] (3) The magnesium alloy substrate from step (1) is placed in the oxidation tank of the micro-arc oxidation equipment using a clamping device. The multi-component composite electrolyte from step (2) is added to the oxidation tank. The magnesium alloy substrate is completely immersed in the multi-component composite electrolyte as the anode, and a stainless steel sheet is used as the cathode. The power supply is set to constant voltage working mode. The micro-arc oxidation process parameters are adjusted for micro-arc oxidation treatment. The process parameters are: voltage 480V, frequency 1300Hz, duty cycle 10%, and oxidation treatment time 23min. During the micro-arc oxidation treatment, a chiller is used to control the electrolyte temperature at 15℃-20℃.

[0078] Performance Analysis:

[0079] (1) Elemental composition analysis of the coating:

[0080] The high-entropy oxide ceramic coating of this embodiment 3 is composed of Mg, Zr, Ti, Al, V, O and F elements, and the specific element contents are shown in Table 3 below:

[0081] Table 3. Surface element content of the high-entropy oxide ceramic coating in Example 3:

[0082] ;

[0083] (2) Coating composition and hardness analysis:

[0084] The high-entropy oxide ceramic coating in Example 3 mainly consists of MgO, ZrO2, TiO2, V2O3, Al2O3 and MgF2. Referring to the hardness test method of GB / T 4340-2009, the load was 25gf, and the hardness of the coating was measured to be 728HV.

[0085] (3) Corrosion resistance analysis:

[0086] The magnesium-lithium alloy with a high-entropy oxide ceramic coating on its surface in Example 3 was subjected to electrochemical polarization testing in a 3.5% NaCl solution. The corrosion current Icorr of the AZ31B magnesium alloy with the high-entropy oxide ceramic coating was 8.956 × 10⁻⁶. - 9 A / cm 2 The high-entropy oxide ceramic coating exhibits a low corrosion current, indicating that the coating has excellent corrosion resistance and provides good corrosion protection.

[0087] Comparative Example 1:

[0088] The difference from Example 1 is that a micro-arc oxidation coating containing only Mg is prepared on the surface of LA103Z magnesium alloy. The preparation method specifically includes the following steps:

[0089] (1) Pretreatment of magnesium alloy substrate: Select LA103Z magnesium alloy sheet with dimensions (length × width × thickness) of 15mm × 15mm × 3mm, and use a sandblasting machine to sandblast the LA103Z magnesium alloy with a sand particle size of 150 mesh and a pressure of 0.3Mpa. Then use compressed air to blow clean the surface of LA103Z magnesium alloy. Then use 320#, 600# and 1000# water-resistant abrasive paper to polish the LA103Z magnesium alloy step by step. Finally, ultrasonically clean it in anhydrous ethanol for 10 minutes and dry it for later use to complete the pretreatment.

[0090] (2) To prepare the electrolyte of this comparative example, 40 g / L sodium citrate, 10 g / L sodium pyrophosphate and 10 mL / L triethanolamine were added to deionized water in sequence, while stirring continuously until completely dissolved, and the electrolyte was prepared.

[0091] (3) The magnesium alloy substrate from step (1) is clamped and placed in the oxidation tank of the micro-arc oxidation equipment. The electrolyte from step (2) is added to the oxidation tank. The magnesium alloy substrate is completely immersed in the electrolyte as the anode and a stainless steel sheet is used as the cathode. The power supply is set to constant voltage working mode. The micro-arc oxidation process parameters are adjusted for micro-arc oxidation treatment. The process parameters are: voltage 500V, frequency 1500Hz, duty cycle 10%, oxidation treatment time 25min. The electrolyte temperature is controlled at 15℃-20℃ during the micro-arc oxidation process using a refrigeration unit.

[0092] Comparative Example 2:

[0093] The difference from Example 1 is that a micro-arc oxidation coating containing two metallic elements, Mg and Zr, is prepared on the surface of LA103Z magnesium alloy. The preparation method specifically includes the following steps:

[0094] (1) Pretreatment of magnesium alloy substrate: Select LA103Z magnesium alloy sheet with dimensions (length × width × thickness) of 15mm × 15mm × 3mm, and use a sandblasting machine to sandblast the LA103Z magnesium alloy with a sand particle size of 150 mesh and a pressure of 0.3Mpa. Then use compressed air to blow clean the surface of LA103Z magnesium alloy. Then use 320#, 600# and 1000# water-resistant abrasive paper to polish the LA103Z magnesium alloy step by step. Finally, ultrasonically clean it in anhydrous ethanol for 10 minutes and dry it for later use to complete the pretreatment.

[0095] (2) To prepare the electrolyte of this comparative example, 40 g / L sodium citrate, 20 g / L ammonium fluorozirconate, 10 g / L sodium pyrophosphate and 10 mL / L triethanolamine were added to deionized water in sequence, while stirring continuously until completely dissolved to obtain the electrolyte.

[0096] (3) The magnesium alloy substrate from step (1) is clamped and placed in the oxidation tank of the micro-arc oxidation equipment. The electrolyte from step (2) is added to the oxidation tank. The magnesium alloy substrate is completely immersed in the electrolyte as the anode and a stainless steel sheet is used as the cathode. The power supply is set to constant voltage working mode. The micro-arc oxidation process parameters are adjusted for micro-arc oxidation treatment. The process parameters are: voltage 500V, frequency 1500Hz, duty cycle 10%, oxidation treatment time 25min. The electrolyte temperature is controlled at 15℃-20℃ during the micro-arc oxidation process using a refrigeration unit.

[0097] Comparative Example 3:

[0098] The difference from Example 1 is that a micro-arc oxidation coating containing three metallic elements, Mg, Zr, and Ti, is prepared on the surface of LA103Z magnesium alloy. The preparation method specifically includes the following steps:

[0099] (1) Pretreatment of magnesium alloy substrate: Select LA103Z magnesium alloy sheet with dimensions (length × width × thickness) of 15mm × 15mm × 3mm, and use a sandblasting machine to sandblast the LA103Z magnesium alloy with a sand particle size of 150 mesh and a pressure of 0.3Mpa. Then use compressed air to blow clean the surface of LA103Z magnesium alloy. Then use 320#, 600# and 1000# water-resistant abrasive paper to polish the LA103Z magnesium alloy step by step. Finally, ultrasonically clean it in anhydrous ethanol for 10 minutes and dry it for later use to complete the pretreatment.

[0100] (2) To prepare the electrolyte of this comparative example, 40 g / L sodium citrate, 20 g / L ammonium fluorozirconate, 20 g / L ammonium fluorotitanate, 10 g / L sodium pyrophosphate and 10 mL / L triethanolamine were added to deionized water in sequence, while stirring continuously until completely dissolved to obtain the electrolyte.

[0101] (3) The magnesium alloy substrate from step (1) is clamped and placed in the oxidation tank of the micro-arc oxidation equipment. The electrolyte from step (2) is added to the oxidation tank. The magnesium alloy substrate is completely immersed in the electrolyte as the anode and a stainless steel sheet is used as the cathode. The power supply is set to constant voltage working mode. The micro-arc oxidation process parameters are adjusted for micro-arc oxidation treatment. The process parameters are: voltage 500V, frequency 1500Hz, duty cycle 10%, oxidation treatment time 25min. The electrolyte temperature is controlled at 15℃-20℃ during the micro-arc oxidation process using a refrigeration unit.

[0102] Performance comparison:

[0103] (1) Corrosion resistance test:

[0104] The high-entropy oxide ceramic coatings on the magnesium alloy surface of Examples 1-3 were used as the test group, and the micro-arc oxidation coatings obtained on the magnesium alloy substrate surface of Comparative Examples 1-3 were used as the control group.

[0105] The test was conducted using an electrochemical workstation with a 3.5% NaCl solution as the corrosive medium. The test results are shown in Table 4.

[0106] Table 4. Corrosion current of the coatings in the test group and the control group:

[0107] ;

[0108] As can be seen from Table 4, under the same experimental conditions, the corrosion current of Examples 1-3 of the present invention is significantly lower than that of the control group. This indicates that compared with the magnesium alloy micro-arc oxidation coating containing only 1-3 alloying elements, the high-entropy oxide ceramic coating on the magnesium alloy surface of the present invention has better corrosion resistance due to the synergistic effect of multiple alloying elements such as Mg, Zr, Ti, Al and V in the high-entropy oxide.

[0109] (2) Coating hardness test:

[0110] The high-entropy oxide ceramic coatings on the magnesium alloy surface of Examples 1-3 were compared with the micro-arc oxidation coatings obtained on the magnesium alloy substrate surface of Comparative Examples 1-3 as a control group.

[0111] Referring to GB / T 4340-2009, the surface hardness of the coating was tested with a load of 25gf. The test results are shown in Table 5.

[0112] Table 5. Hardness of the coatings in the test group and the control group:

[0113] ;

[0114] As can be seen from Table 5, under the same experimental conditions, the coating hardness of Examples 1-3 of the present invention is significantly higher than that of the control group. This indicates that compared with the magnesium alloy micro-arc oxidation coating containing only 1-3 alloying elements, the high-entropy oxide ceramic coating on the magnesium alloy surface of the present invention has higher hardness due to the synergistic effect of multiple alloying elements such as Mg, Zr, Ti, Al and V in the high-entropy oxide.

Claims

1. A high-entropy oxide ceramic coating on the surface of a magnesium alloy, characterized in that, The elemental composition of the high-entropy oxide ceramic coating includes metallic elements, O and F, wherein the metallic elements are Mg, Zr, Ti, Al and V. The high-entropy oxide ceramic coating is grown in situ on the surface of a magnesium alloy substrate by micro-arc oxidation treatment and is composed of MgO, ZrO2, TiO2, Al2O3, V2O3 and MgF2, with a thickness of 15μm-20μm.

2. The high-entropy oxide ceramic coating on a magnesium alloy surface as described in claim 1, characterized in that, The atomic percentages of the elements in the high-entropy oxide ceramic coating are: Mg: 14.5%-23.0%, Zr: 6.0%-7.5%, Ti: 5.5%-7.0%, Al: 5.0%-6.0%, V: 5.5%-6.5%, O: 48.0%-52.5%, F: 5.5%-7.0%.

3. The high-entropy oxide ceramic coating on a magnesium alloy surface as described in claim 1, characterized in that, Magnesium alloy matrices include LA103Z, AZ31B, and ZK61M.

4. A method for preparing a high-entropy oxide ceramic coating on a magnesium alloy surface as described in claim 1, characterized in that, The specific steps include: (1) Pretreatment of magnesium alloy matrix; (2) Prepare a multi-component composite electrolyte containing the metal elements required for the high-entropy oxide ceramic coating; (3) The magnesium alloy substrate from step (1) is clamped in a hanger and placed in the oxidation tank of the micro-arc oxidation equipment. The multi-component composite electrolyte from step (2) is added to the oxidation tank. The magnesium alloy substrate is completely immersed in the multi-component composite electrolyte for micro-arc oxidation treatment.

5. The method for preparing a high-entropy oxide ceramic coating on a magnesium alloy surface as described in claim 4, characterized in that, Step (1) pretreatment involves sandblasting the magnesium alloy substrate with a sandblasting machine, then cleaning the magnesium alloy surface with compressed air, and then polishing the magnesium alloy step by step with low, medium and high grit water-resistant sandpaper. Finally, ultrasonic cleaning is performed, and the substrate is dried for later use.

6. The method for preparing a high-entropy oxide ceramic coating on a magnesium alloy surface as described in claim 5, characterized in that, The sand used for sandblasting is zirconium oxide with a particle size of 150 mesh and a pressure of 0.3 MPa. Water-resistant sandpaper with low, medium, and high mesh counts is available in 320#, 600#, and 1000#.

7. The method for preparing a high-entropy oxide ceramic coating on a magnesium alloy surface as described in claim 4, characterized in that, Step (2) The multi-component composite electrolyte is composed of sodium citrate, ammonium fluorozirconate, ammonium fluorotitanate, ammonium fluoroaluminate, ammonium metavanadate, sodium pyrophosphate, and triethanolamine.

8. The method for preparing a high-entropy oxide ceramic coating on a magnesium alloy surface as described in claim 7, characterized in that, The specific preparation process of the multi-component composite electrolyte is as follows: 20 g / L-40 g / L sodium citrate, 10 g / L-20 g / L ammonium fluorozirconate, 10 g / L-20 g / L ammonium fluorotitanate, 10 g / L-20 g / L ammonium fluoroaluminate, 10 g / L-20 g / L ammonium metavanadate, 5 g / L-10 g / L sodium pyrophosphate, and 10 mL / L triethanolamine are added sequentially to deionized water, while continuously stirring until completely dissolved to obtain the multi-component composite electrolyte.

9. The method for preparing a high-entropy oxide ceramic coating on a magnesium alloy surface as described in claim 4, characterized in that, In step (3), the magnesium alloy substrate is used as the anode, the stainless steel sheet is used as the cathode, the power supply is set to constant voltage working mode, the electrolyte temperature is controlled, and the process parameters of micro-arc oxidation treatment are adjusted.

10. The method for preparing a high-entropy oxide ceramic coating on a magnesium alloy surface as described in claim 9, characterized in that, The process parameters for micro-arc oxidation are as follows: voltage 450V-500V, frequency 1000Hz-1500Hz, duty cycle 10%, oxidation time 20min-25min, and the electrolyte temperature is controlled at 15℃-20℃ during the micro-arc oxidation process using a chiller.

Citation Information

Patent Citations

  • High-entropy composite oxide hydrogen-resistant coating and preparation method thereof

    CN115971011A

  • Surface-ceramized high-entropy alloy material and preparation method thereof

    CN109252199A

  • Preparation method of high-entropy ceramic coating

    CN111254379A